2015
DOI: 10.13065/jksdh.2015.15.02.261
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and influencing factors on oral health awareness, oral health behavior, self-esteem and OHIP-14 in childcare teachers

Abstract: Objectives:The purpose of the study is to investigate the correlation and influencing factors of oral health awareness, oral health behaviors, self-esteem and OHIP-14. Methods: A self-reported questionnaire was filled out by 313 childcare teachers in Jeonnam from June 4 to 14, 2013. The questionnaire consisted of 3 questions of general characteristics, 4 questions of occupation, 1 question of oral health education experience, and 1 question of oral health education participation. The instrument for awareness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This study showed that inmates with high self-esteem (41.10 points) had higher OHIP-14 scores than did inmates with low self-esteem (38.65 points), but the difference was not statistically significant. This finding was similar to that of previous studies in childcare teachers [52], a general adult population [53], and orthodontic patients [54,55].…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that inmates with high self-esteem (41.10 points) had higher OHIP-14 scores than did inmates with low self-esteem (38.65 points), but the difference was not statistically significant. This finding was similar to that of previous studies in childcare teachers [52], a general adult population [53], and orthodontic patients [54,55].…”
Section: Discussionsupporting
confidence: 92%
“…Adopting a healthy lifestyle during adolescence is easier and has a long-lasting impact on overall health in adulthood [2]. As health behaviors in adolescents have received more attention, recent studies have focused on factors influencing oral health in adolescents [3]. In the Republic of Korea, the Korean National Health and Nutrition Examination Survey, Korean National Oral Health Status Survey, and Korea Youth Risk Behavior Web-Based Survey (KYRBS) have been conducted to study health behaviors in adolescents and include oral health-related questions, making it possible to determine their oral health status.…”
Section: Introductionmentioning
confidence: 99%
“…According to a survey on the comprehensive situation of Korean children conducted in 2013 7) , 12) reported that the higher the level of perceived stress among adolescents, the lower their quality of life related to oral health. A number of studies that considered psychosocial factors, such as self-worth and support from family and friends, have investigated the significance of associations among the level of stress in adults, self-worth, oral health behaviors, and oral health-related quality of life 13,14) ; however, very few studies have used psychological variables related to children. Therefore, it is necessary to investigate the effects of psychological factors on children's oral health after considering psychosocial and oral health behavioral factors, which are determinants of oral health, using indices that reflect various psychological characteristics including stress.…”
Section: Introductionmentioning
confidence: 99%